Problems of Beckett’s Early Poetics - Fernández, José Francisco (ABEI Journal, 2011)
Samuel Beckett’s first novel, Dream of Fair to Middling Women, has been generally defined since its publication in 1992 as Beckett’s consciousdeparture from the narrative tradition in the West. Critics have pointed out the novel’s disregard for unity, the absence of a central plan, the range of unstable characters or the undermining authorial interventions. The object of this essay is to extend the argument further by examining Dream in terms of Mikhail Bakhtin’s ideas on the novel, as they were exposed in Problems of Dostoevsky’s Poetics. I will try to argue that Dream corresponds to the dismantling of an ideal in narrative art, defined by Bakhtin as the polyphonic novel. I will also highlight the features that make of Dream an anti-text in which the Irish writer explored the limits of the relationships he could have with his readers.